Antenatal Health Care Service Utilization in Slum Areas of Pokhara Sub-Metropolitan City, Nepal - Sharma, D; Pokharel, H P; Budhathoki, S S; Yadav, B K; Pokharel, P K (Journal of Nepal Health Research Council, 2016)
Background: Half a million women die every year due to pregnancy and childbirth in the world. Among these death, 99% occur in the low and middle income countries. Antenatal care (ANC) provides an opportunity to deliver different services which are important in improving maternal survival.Methods: A descriptive cross sectional study was conducted from September 2012 - February 2013 among 400 married women of reproductive age group. A pre-tested structured questionnaire were used and data were analyzed using Statistical Package for Social Science(SPSS) for windows version 18.0. Frequency, crude and adjusted odds ratios and confidence intervals were performed.Results: Nearly 27% had four or more antenatal health care utilization(ANC) visits on appropriate time according to schedule of World Health Organization(WHO). In logistic regression, ANC users were found to be more/less likely to be in age group 20 – 35 years (AOR =2.825, 95% CI: 1.166-6.843), education of spouse (AOR 0.361, 95% CI : 0.130–1.000), occupation of spouse (AOR = 0.261, 95% CI: 0.093 –0.739), monthly income of family > 20,000Nrs (AOR = 2.190, 95% CI: 1.041–4.606), planned pregnancy (AOR = 2.417, 95% CI: 1.047 –5.609), death of child (AOR = 3.153, 95% CI: 1.112 –8.944).Conclusions: This study demonstrated low antenatal care service utilization. Hence, there is a need to increase the availability and accessibility of antenatal care to all women. Keywords: Antenatal care (ANC); appropriate time of visit; child birth; pregnancy; reproductive age.